2016
DOI: 10.1161/jaha.116.004031
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Inhibits Atherosclerosis by Promoting Endothelial Proliferation Through microRNA126‐5p

Abstract: Background Irisin is a newly discovered myokine that has been considered a promising candidate for the treatment of cardiovascular disease through improving endothelial function. However, little is known about the role of irisin in the progression of atherosclerosis. Methods and Results We used a carotid partial ligation model of apolipoprotein E–deficient mice fed on a high‐cholesterol diet to test the anti‐atherosclerosis effect of irisin. Irisin treatment significantly suppressed carotid neointima formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 40 publications
1
42
1
Order By: Relevance
“…Lee et al (20) showed that circulating irisin levels were negatively associated with carotid intima-media thickness in peritoneal dialysis patients. In some rodent studies, the mechanisms underlying the protective effects of irisin on atherosclerosis are clarifying (11,12,21). However, our findings are in conflict with those of a number of studies showing that circulating irisin may negatively affect cardiovascular disease or risk factors.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Lee et al (20) showed that circulating irisin levels were negatively associated with carotid intima-media thickness in peritoneal dialysis patients. In some rodent studies, the mechanisms underlying the protective effects of irisin on atherosclerosis are clarifying (11,12,21). However, our findings are in conflict with those of a number of studies showing that circulating irisin may negatively affect cardiovascular disease or risk factors.…”
Section: Discussioncontrasting
confidence: 79%
“…Irisin is secreted into the circulation after cleavage from the membrane protein FNDC5 and activates expression of mitochondrial uncoupling protein-1 (UCP-1) and "browning" of white adipose tissue (8), leading to increased insulin sensitivity, improved glucose tolerance, lower body weight, and decreased fat mass (9,10). Several studies have shown that irisin also promotes endothelial function and inhibits atherosclerosis (11,12). However, to the best of our knowledge, the association between myokines, especially irisin, and the characteristics of coronary plaques is still unclear.…”
mentioning
confidence: 99%
“…Several studies have also suggested that irisin treatment reduced the degree of carotid and aortic atherosclerotic plaque in apolipoprotein E-knock out mice, an atherosclerotic model [ 50 , 51 , 52 ]. These studies demonstrated that irisin may suppress neointima formation, endothelial injury, and inflammation in the atherosclerotic vasculature, implying a potential role of irisin in treating atherosclerosis [ 50 , 51 , 52 ]. The findings of the previous studies suggest that irisin may be a therapeutic target for vascular complications and dysfunction induced by metabolic abnormality.…”
Section: The Potential Role Of Irisin In Vascular Reactivity and Amentioning
confidence: 99%
“…Liu et al found that Fndc5 deficiency aggravated whereas FNDC5 overexpression prevented obesity-related hyperlipemia, hepatic lipid accumulation, and impaired fatty acid oxidation and autophagy in the liver [20]. Except for the beneficial role in metabolic disorders, recent studies also implicated that FNDC5/Irisin was involved in regulating various cardiovascular diseases, such as atherosclerosis, hypertension, myocardial ischemia/reperfusion injury, and cardiac hypertrophy [21][22][23][24]. Besides, numerous researches verified that FNDC5 overexpression or irisin supplementation could preserve mitochondrial function and attenuate oxidative damage as well as cell apoptosis [25,26].…”
Section: Introductionmentioning
confidence: 99%